Hambatan dalam Implementasi Program Pembelajaran pada Satuan Pendidikan Nonformal di Sanggar Kegiatan Belajar (SKB) Kota Serang. - sitorus, arman; Sitorus, Arman Mangaratua; Permana, Gilang; Nisrina, Amelia Dea; Mustaqim, Maulana; Ganiadi, Mochamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify and describe the various obstacles faced in the implementation of non-formal education learning programs at the Learning Activity Center (SKB) of Serang City. The method applied in this study is a qualitative approach with descriptive research type, through semi-structured interviews, observation, and documentation involving the head of SKB, pamong belajar, and administrative staff. The research findings reveal that there are a number of significant obstacles, including: (1) limited number of educators or learning assistants, (2) less than optimal mastery of subject matter by learning assistants, (3) low competence of education personnel in designing programs, and (4) limited operational budget allocations for the implementation of learning programs. These constraints affect the effectiveness of the program and the quality of education services provided to the community. This study recommends the need to increase the number of teaching staff, organize training for learning assistants, and increase budget allocations to support the sustainability of non-formal education programs at SKB Serang City.